The efficacy of hyaluronic acid treatment on induced periodontitis in rats exposed to gamma radiation - Salwa Farid Ahmed; Amira Ibrahim Sayed; Heba Abdelfatah; Lobna Mohamed Abdel-Aziz (Scientific Reports)
Abstract The periodontium is one of the radiation-sensitive tissues; the periodontal membrane’s vascularity and cellularity were reduced, and the danger of losing periodontal attachment was raised. This study was performed to evaluate the efficacy of hyaluronic acid treatment on induced periodontitis in rats exposed to gamma radiation radiographically and histopathologically. A total number of 30 adult male Albino rats were divided randomly into five groups (n = 6). Group 1 (C): received neither irradiation nor treatment. Group 2 (P): was subjected to induced periodontitis. Group 3 (PT): subjected to induced periodontitis with hyaluronic acid treatment. Group 4 (RP): received a single dose of total cranium irradiation 20 Gy with induced periodontitis. Group 5 (RPT): received a single dose of total cranium irradiation 20 Gy with induced periodontitis and hyaluronic acid treatment. All animals were euthanized, and the outcomes of treatment were evaluated radiographically by cone beam computed tomography (CBCT) and histopathologically. Results: Comparison of the five groups about bone density by one-way ANOVA showed a significant difference among groups (P < 0.001). The highest bone density values were measured in Group (PT) (1245 ± 22.86), while the lowest bone density values were measured in Group (RP) (926 ± 31.47). Using post hoc analysis for pairwise comparisons showed that Group (PT) and Group (RPT) have significantly higher values than Group (P) and Group (RP) (P < 0.001). Histologically, the group (RPT) shows a new formation of irregular connective tissue fibers of the periodontal ligament (PDL) with an area of distortion, fibrous marrow spaces with wide osteocyte lacunae without nuclei, and Haversian canals with empty blood vessels. The radiographic and histopathological findings of using HA as a topical application in rats subjected to induced periodontitis and exposed to gamma radiation revealed enhanced healing ability of the periodontal tissue with restoration of the bone density. Depending on these results, HA could be used as an adjunct local delivery agent for periodontal-affected patients receiving radiotherapy.